Sociological Perspective and Legal Protection of Customary Land: Solution to Determination of Traditional Forest in Indonesia - Sukirno, Sukirno; Adhim, Nur (International Journal of Criminology and Sociology, 2021)
This study is motivated by the perspective of government officials and the mechanism for determining customary forests which is often the cause of conflict between indigenous peoples and plantation entrepreneurs who accept concessions from the government. The aims of this study are to evaluate the legal positivism perspective that continued domein verklaring during the Dutch colonialism saw customary forests as state forests as long as they had not been determined by the government so that they could be concessioned to plantation entrepreneurs. The results showed that in order to prevent conflicts and to simplify and speed up the mechanism for determining customary forests, an idea is offered to apply the legal processing (rechtsverwerking) analogy in customary law that has been accepted by the national land law. The physical control of customary forests by customary communities by collecting products, utilizing and conserving the forest, regulated in customary law and not denied by indigenous peoples, who border, is sufficient as a sign that the customary forest is under the control of the customary community concerned. Likewise, for the stipulation mechanism, it is necessary to give authority to the local government to be able to determine customary forests.